Updating the risk profile of fatal head trauma: an autopsy study with focus on age- and sex-dependent differences - Kronsbein, Katharina; Karger, Bernd; Budczies, Jan; Pfeiffer, Heidi; Wittschieber, Daniel (International journal of legal medicine, 2020)
Fatal head trauma (FHT) represents one of the most frequent causes of death diagnosed in forensic pathology. However, profound statistic autopsy data on FHT is still sparse. Therefore, the purpose of this study was to investigate the circumstances and injury patterns of FHT with particular focus on age and sex, and additionally, to describe a recent risk profile of FHT. To this end, the forensic autopsy records of each FHT case at a large German university hospital during a 10-year period (2006-2015) were analyzed retrospectively (n = 372). The male-female ratio was 2.6:1. Regarding median age, females were 12.5 years older than males. Traffic-associated FHT represents the major mechanism of death, followed by fall-associated FHT. While accident was the major manner of death and presented a similar distribution of age and sex, homicides were the only subgroup with a significantly lower ratio between males and females. Skull fractures occurred in 78.2% and intracranial hemorrhages in 80.6% of all cases. In summary and partly in contrast to clinical data on head trauma, FHT still occurs predominantly in male individuals under the age of 45 years, in the context of traffic accidents and affected by alcohol intake. Improvements in traffic security as well as continuing surveillance of the incidence of FHT by forensic autopsies are necessary to further reduce the incidence of FHT.
Published online: 18 November 2019
Gesehen am 22.04.2020